2023
DOI: 10.1186/s12909-023-04436-5
|View full text |Cite
|
Sign up to set email alerts
|

Using three-dimensional printed models for trainee orbital fracture education

Abstract: Background Three-dimensional printing is an underutilized technology in ophthalmology training; its use must be explored in complex educational scenarios. This study described a novel approach to trainee education of orbital fracture repair utilizing three-dimensional (3D) printed models as a teaching tool. Methods Ophthalmology residents and oculoplastic fellows from multiple training institutions underwent an educational session on orbital fractu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…For instance, Lichtenstein’s team developed a 3D-printed tactile and structurally mimicking model incorporating both hard and soft tissues for orbital surgical training [ 109 ]. In a survey by Rama et al, more than 84% of students taught with 3D-printed orbital fracture models found them useful for enhancing visual–spatial skills, anatomy education, and surgical training [ 110 ]. Beyond orbital fracture training, 3D-printed eye models prove valuable for strabismus surgery training, with surveys confirming their fidelity compared to conventional rabbit head models.…”
Section: 3d Printing In Ophthalmic Prototyping and Simulationmentioning
confidence: 99%
“…For instance, Lichtenstein’s team developed a 3D-printed tactile and structurally mimicking model incorporating both hard and soft tissues for orbital surgical training [ 109 ]. In a survey by Rama et al, more than 84% of students taught with 3D-printed orbital fracture models found them useful for enhancing visual–spatial skills, anatomy education, and surgical training [ 110 ]. Beyond orbital fracture training, 3D-printed eye models prove valuable for strabismus surgery training, with surveys confirming their fidelity compared to conventional rabbit head models.…”
Section: 3d Printing In Ophthalmic Prototyping and Simulationmentioning
confidence: 99%